Use of Maternal Health Services and Utilization of Modern Contraceptive Methods Among Cohabiting Women, Peru-2023 - Soria-Gonzales, Lalescka Araceli (2026)
Objective: To determine the association between the use of maternal health services and the utilization of modern contraceptive methods among cohabiting women in Peru-2023. Methods: Data from the 2023 Demographic and Family Health Survey (ENDES) were analyzed. The study population included women aged 15 to 49 years who had at least one birth in the last five years and were married or living with a partner. The variables used to assess maternal health services were : number of antenatal care visits, place of antenatal care, place of delivery, postpartum medical check-up, and type of provider performing the postnatal check-up. The association was estimated using prevalence ratios (PR) with 95% confidence intervals, obtained through  generalized linear models with a Poisson distribution, both crude and adjusted. Results: Delivery in public facilities (aPR=1.17; 95% CI: 1.09–1.26) and private facilities (aPR=1.14; 95% CI: 1.05–1.24) was associated with higher utilization of modern contraceptive methods compared with home delivery. Likewise, postpartum medical check-up was significantly associated with modern contraceptive use (aPR = 1.38; 95% CI: 1.19-1.60) compared with women who did not receive it..Conclusion: Among the indicators of maternal health service use,  place of delivery and postpartum medical check-up were associated with greater use of modern contraceptive methods.